Levodopa-responsive dystonia caused by biallelic PRKN exon inversion invisible to exome sequencing. Issue 3 (6th September 2021) - Mor-Shaked, Hagar; Paz-Ebstein, Emuna; Basal, Adily; Ben-Haim, Simona; Grobe, Hanna; Heymann, Sami; Israel, Zvi; Namnah, Montaser; Nitzan, Anat; Rosenbluh, Chaggai; Saada, Ann; Tzur, Tomer; et al.
Abstract: Biallelic pathogenic variants in PRKN ( PARK2 ), encoding the E3 ubiquitin ligase parkin, lead to early-onset Parkinson's disease. Structural variants, including duplications or deletions, are common in PRKN due to their location within the fragile site FRA6E. These variants are readily detectable by copy number variation analysis. We studied four siblings with levodopa-responsive dystonia by exome sequencing followed by genome sequencing. Affected individuals developed juvenile levodopa-responsive dystonia with subsequent appearance of parkinsonism and motor fluctuations that improved by subthalamic stimulation. Exome sequencing and copy number variation analysis were not diagnostic, yet revealed a shared homozygous block including PRKN . Genome sequencing revealed an inversion within PRKN, with intronic breakpoints flanking exon 5. Breakpoint junction analysis implicated non-homologous end joining and possibly replicative mechanisms as the repair pathways involved. Analysis of cDNA indicated skipping of exon 5 (84 bp) that was replaced by 93 bp of retained intronic sequence, preserving the reading frame yet altering a significant number of residues. Balanced copy number inversions in PRKN are associated with a severe phenotype. Such structural variants, undetected by exome analysis and by copy number variation analysis, should be considered in the relevant clinical setting. These findings raise the possibility that PRKN structural variants are more common than currently estimated. Abstract : Mor-Shaked et al. report a homozygous copy number neutral inversion in PRKN, encoding parkin, in a family with juvenile levodopa-responsive dystonia and parkinsonism. The authors demonstrate that the inversion leads to exon skipping and intronic inclusion, and highlight the importance of whole-genome sequencing in exome-negative cases. Graphical Abstract: